Gejala Demam Perspektif Dunia Kedokteran Muslim: Studi Tahkrij dan Syarah Hadits - Lespi Nurul Izati; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
This study aims to discuss the takhrij and syarah hadith related to fever as originating from evil vapors. This study uses a qualitative approach that emphasizes literature review through the takhrij and syarah hadith methods with contemporary analysis. The results of this study indicate that the quality status of the hadith about fever comes from the steam of hell with authentic quality because it has met the criteria for authenticity of sanad and authenticity of matan hadith. This hadith is considered authentic because all the narrators are dzabit and adl (tsiqot). Meanwhile, the hadith syarah shows that the treatment of fever can be done using water or better known as a compress, which is one of the methods of treatment that was used by the Prophet Saw and is still effective. This study concludes that the hadith about fever as coming from the steam of hell is acceptable (maqbul) so that it can be used as evidence for Islamic practice.